Becoming Deu-Hu-Moid: Tinjauan Teologi Proses tentang Eksistensi dan Relasi Manusia dengan Humanoid di Era Society 5.0 - Evans Sagala; Frans Best Soma Marpaung (Indonesian Journal of Theology, 2026)
The emergence of humanoid technologies in the era of Society 5.0 raises new theological questions concerning the relationship among God, humanity, and artificial beings. This article proposes Becoming Deu-Hu-Moid as a constructive theological model for interpreting this relationship. Drawing on Catherine Keller’s theology of becoming and the doctrine of creatio continua, the study examines the presence of humanoid technologies within the ongoing dynamism of creation. The article argues that humanoids should not be understood as spiritual subjects or as substitutes for human relationality with God. Rather, they function as limited relational participants whose instrumental capacities may enrich pastoral practices and support the church’s participation in the missio Dei. Within this construction, the relationship among Deus (God), Hu (humanity), and Moid (humanoid) may be imagined as a co-creative relational network emerging within the open and dynamic process of becoming, while remaining attentive to the ambiguities and limits of humanoid technological mediation